The effect of high-definition transcranial direct current stimulation intensity on motor performance in healthy adults: a randomized controlled trial - Lerner, Ohad (J Neuroeng Rehabil, 2021)
BACKGROUND: The results of transcranial direct current stimulation (tDCS) studies that seek to improve motor performance for people with neurological disorders, by targeting the primary motor cortex, have been inconsistent. One possible reason, among others, for this inconsistency, is that very little is known about the optimal protocols for enhancing motor performance in healthy individuals. The best way to optimize stimulation protocols for enhancing tDCS effects on motor performance by means of current intensity modulation has not yet been determined. We aimed to determine the effect of current intensity on motor performance using–for the first time–a montage optimized for maximal focal stimulation via anodal high-definition tDCS (HD-tDCS) on the right primary motor cortex in healthy subjects. METHODS: Sixty participants randomly received 20-min HD-tDCS at 1.5, 2 mA, or sham stimulation. Participants’ reaching performance with the left hand on a tablet was tested before, during, and immediately following stimulation, and retested after 24 h. RESULTS: In the current montage of HD-tDCS, movement time did not differ between groups in each timepoint. However, only after HD-tDCS at 1.5 mA did movement time improve at posttest as compared to pretest. This reduction in movement time from pretest to posttest was significantly greater compared to HD-tDCS 2 mA. Following HD-tDCS at 1.5 mA and sham HD-tDCS, but not 2 mA, movement time improved at retest compared to pretest, and at posttest and retest compared to the movement time during stimulation. In HD-tDCS at 2 mA, the negligible reduction in movement time from the course of stimulation to posttest was significantly lower compared to sham HD-tDCS. Across all groups, reaction time improved in retest compared to pretest and to the reaction time during stimulation, and did not differ between groups in each timepoint. CONCLUSIONS: It appears that 2 mA in this particular experimental setup inhibited the learning effects. These results suggest that excitatory effects induced by anodal stimulation do not hold for every stimulation intensity, information that should be taken into consideration when translating tDCS use from the realm of research into more optimal neurorehabilitation. Trial registration: Clinical Trials Gov, NCT04577768. Registered 6 October 2019 -Retrospectively registered, https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000A9B3&selectaction=Edit&uid=U0005AKF&ts=8&cx=buucf0. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12984-021-00899-z.